Magnetic field analytical calculation method for radial unite of a combined magnetic bearing - Xiaojun Ren; Ming Feng; Tianming Ren (IET Electric Power Applications)
Abstract Combined magnetic bearing with radial and axial unites is an important supporting element for high speed and high energy density motor. Accurate calculation of the magnetic field is a key to design and optimise a Combined Radial and Axial Magnetic Bearing (CRAMB). This study focuses on magnetic field analytical calculation method for radial Unite of CRAMB. The analytical calculation model of magnetic field is based on subdomain method. The Laplace's equations in the air‐gap subdomain are solved by the variable separation method. The magnetic field of magnetic bearing with large diameter rotor is analysed and calculated in Cartesian coordinate system. Considering the influence of curvature the magnetic field distribution of magnetic bearing with small diameter rotor is deduced and calculated analytically in polar coordinate system. The effectiveness of the analytical method is verified by finite element and experimental results.